NUTRITIONAL AND PREVENTIVE ASPECTS OF SECONDARY SCHOOL STUDENTS' LIFESTYLES IN TERESINA / PI (Fiep Bulletin - online, 2015)
This work underscores the need for reflections and attitudes about the practices and challenges of physical education related to health promotion and explores the issue of health and aspects related to quality and style of life, such as the conceptions of secondary school students in terms of awareness regarding healthy habits such as, for example, Nutrition and Preventive Behavior of students of the 3rd year of secondary school at a public school in the city of Teresina / PI, in the period 02-13 December 2013. It is a descriptive and quantitative and qualitative survey and has been applied to 58 students with an average age of 17.5 years, 35 female and 23 male. In this case the Profile of Individual Lifestyle (PEVI) was used. The results have shown that their nutrition consisted of a balanced diet, including at least five vegetables in their daily diet, but with the presence of a high consumption of fatty foods and sweets, which are foods related the health disorders. As to prevention in terms of health, we have found a worrying statistic indicating the consumption of alcoholic beverages, a factor responsible for many problems of public health.
Keywords: Lifestyle; Health; Education.